2023
DOI: 10.3390/vaccines11020213
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Second COVID-19 Vaccine Booster Dose in the Elderly

Abstract: Background: We analyzed coronavirus disease 2019 (COVID-19) vaccine efficacy in older persons who received the second booster compared to unvaccinated people and those receiving only a single COVID-19 vaccine booster. Methods: We collected information on vaccine efficacy from the ongoing Italian nationwide COVID-19 vaccination campaign in subjects aged 80 years or older from official data published by the Italian National Institute of Health. Results: The second vaccine booster maintained high effectiveness ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…During the vaccination campaign, a multitude of data from randomized controlled trials (RCTs) and real-world observational studies emerged, providing insights into the efficacy and safety of registered vaccines globally [ 32 ]. The evidence available today demonstrates the effectiveness of COVID-19 vaccines in reducing the risk of developing symptomatic disease, surpassing the efficacy rates of other vaccines, such as influenza vaccines (around 50–60% efficacy), and effectively preventing severe disease, hospitalizations, and deaths [ 22 , 33 , 34 ] associated with COVID-19. In 2021, across 90 countries, Liang et al [ 35 ] showed that for every 10% increase in COVID-19 vaccine coverage, the mortality rate could be reduced by 8%.…”
Section: Introductionmentioning
confidence: 99%
“…During the vaccination campaign, a multitude of data from randomized controlled trials (RCTs) and real-world observational studies emerged, providing insights into the efficacy and safety of registered vaccines globally [ 32 ]. The evidence available today demonstrates the effectiveness of COVID-19 vaccines in reducing the risk of developing symptomatic disease, surpassing the efficacy rates of other vaccines, such as influenza vaccines (around 50–60% efficacy), and effectively preventing severe disease, hospitalizations, and deaths [ 22 , 33 , 34 ] associated with COVID-19. In 2021, across 90 countries, Liang et al [ 35 ] showed that for every 10% increase in COVID-19 vaccine coverage, the mortality rate could be reduced by 8%.…”
Section: Introductionmentioning
confidence: 99%
“…So, the mutated antigen is the culprit, not the original antigen (Figure 1D). [25] conducted a review of the analyses of COVID-19 vaccine efficacy in older persons who received the second booster compared to unvaccinated people and those who received only a single COVID-19 vaccine booster. The second vaccine booster maintained high effectiveness against adverse COVID-19 outcomes such as hospitalization, intensive care unit admission, and death (i.e., between 77 and 86%) and also showed an efficacy around 10% higher than the single booster.…”
Section: Immunologic Reasons Challenging Oas Theorymentioning
confidence: 99%
“…The efficacy of the second vaccine booster declined over time, decreasing by 33–46% when assessed at >120 days from administration. The results of these ad interim analyses of the ongoing Italian nationwide COVID-19 vaccination campaign suggested that regular boosting with COVID-19 vaccines may be advisable for older persons [ 25 ].…”
Section: Introductionmentioning
confidence: 99%